Respiratory Disorders Associated with Occupational Inhalational Exposure to Bioaerosolsamong WastewaterTreatment Workers of Petrochemical Complexes - Jahangiri, M (Int J Occup Environ Med, 2015)
BACKGROUND: Workers in wastewater treatment plants are exposed to a wide range of chemicals as well as biological contaminants. OBJECTIVE: To ascertain whether exposure to bio-aerosols under the normal working conditions in wastewater treatment plants is associated with any significant changes in the prevalence of respiratory symptoms and lung function capacities. METHODS: 198 employees of wastewater treatment plants and 99 unexposed persons were studied. American thoracic society (ATS) standard respiratory symptom questionnaire was used to determine the prevalence of respiratory symptoms. Pulmonary function tests were conducted for each participant. RESULTS: The prevalence of respiratory symptoms among exposed persons was significantly higher than that of unexposed people. Mean values of most pulmonary function test parameters were significantly lower in the exposed compared to the comparison group persons. CONCLUSION: Increased prevalence of respiratory symptoms and decrements in pulmonary function test parameters may be attributed to exposure to bio-aerosols released from wastewater treatment plants.